Pengembangan Hunian Pendukung Potensi Wisata Kawasan Pesisir di Tanjung Bayang, Kota Makassar - Yuniza Pridanti; Shirly Wunas; Mimi Arifin (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2017)
The strategic position of the beach tends to be neglected by the development of informal dwellings in the Tanjung Bayang Coastal Area that has not yet paid attention to the rules of building layout. The purpose of this study was to identify residential sites, tourism facilities, accessibility, tourism support infrastructure, economic, social and cultural aspects of the area management system, and to arrange directions for the development of residential tourism potential supporters in Tanjung Bayang. Data collection methods used are, field observations, questionnaires, interviews, and literature studies. The data obtained is then processed using descriptive analysis techniques with qualitative, quantitative, comparative, and spatial analysis approaches. The results of this study indicate that, dwelling sites have a relatively low density with a distance between houses ≤ 2m. Non-stage footprint is located on the border area of ​​the beach, but safe from high tide. The tourist support facilities (bale-bale) tend to be dense (5 units / 1 roof) and the rinse building has not served the entire area. access to the area is a function of local roads that lie between the walls of real estate, not yet equipped with markers and pedestrian paths. There is no TPS or waste disposal depot. The electricity network for buildings is adequate, but there are no lighting for bale-bales and rental residences. The dominant community works and utilizes beach facilities as a livelihood. The proposed concept of directives is the development of residential houses into rental housing and the development of facilities, infrastructure, accessibility, and community-based area management systems.